2019
DOI: 10.1007/bf03546072
|View full text |Cite
|
Sign up to set email alerts
|

Ground nesting birds in roadside borders of the Argentine Pampas: habitat use and predation risk of artificial nests

Abstract: Habitat loss and fragmentation have led to grassland bird declines, with ground nesters particularly vulnerable. Roadsides could provide habitat, although their suitability depends on several roadside and field characteristics. Vegetation structure determines foraging and nesting site availability. In addition, road delimits sharp edges where the activity of nest predators is usually higher, whereas herbaceous vegetation determines ground nest concealment. Trees could provide lookouts to predators, and modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Furthermore, we found an effect of distance to patch edge, with interior nests being more predated than edge nests. Although these results were contrary to our expectations, they are in accordance with the pattern recently found by Depalma and Mermoz (2019), who evaluated the effect of distance to a road on predation of artificial nests in the Pampas region. In our case, the main predators were small mammals (82.8% of predated nests).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, we found an effect of distance to patch edge, with interior nests being more predated than edge nests. Although these results were contrary to our expectations, they are in accordance with the pattern recently found by Depalma and Mermoz (2019), who evaluated the effect of distance to a road on predation of artificial nests in the Pampas region. In our case, the main predators were small mammals (82.8% of predated nests).…”
Section: Discussionsupporting
confidence: 81%
“…tussock-scale). For southeastern South American grasslands, studies on artificial nests evaluated types of predators and, particularly, the effect of grazing (Cozzani & Zalba 2012), nest height (Cardoni et al 2012), fire intensity (Bahía & Zalba 2019), and proximity to a road and vegetation structure (Depalma & Mermoz 2019).…”
mentioning
confidence: 99%
“…By contrast, some studies have found no effect (Huhta, 1995; Bechet, Isenmann & Gaudin, 1998; Mettenbrink, Dreitz & Knopf, 2006; Svobodová, Šálek & Albrecht, 2007) or a positive effect of road proximity on nest survival (Delgado García, Arévalo & Fernández‐Palacios, 2005; Angkaew et al ., 2019; da Silva et al ., 2019). Nest predation on road verges involves a complex interaction among: ( i ) the type of infrastructure, with nest predation higher near dirt roads (DeGregorio, Weatherhead & Sperry, 2014); ( ii ) roadside structure (Bergin, Best & Freemark, 1997; Shochat et al ., 2005), with perches such as trees increasing nest predation and tall grass reducing it (Depalma & Mermoz, 2019); ( iii ) traffic volume, with higher traffic loads decreasing nest predation relative to birds breeding close to medium‐to‐low‐traffic roads (Pescador & Peris, 2007); and ( iv ) predator traits, with human‐tolerant or bold predators showing increased foraging activity along road corridors (Pedersen et al ., 2011; Khamcha, Powell & Gale, 2018). However, it is necessary to point out that the literature on nest predation is largely dominated by studies on birds, with only two studies focused on another taxon (turtles).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, their roadsides are often unnecessarily mown, fumigated or even cropped to increase agricultural yields. Argentine Pampas' roadsides have a high conservation value: it has been reported that their vegetation is similar to the original vegetation of the region (Herrera et al 2017, Depalma & Mermoz 2019 and that they host great plant and pollinator diversity (Herrera et al 2020, Monasterolo et al 2020). In addition, birds are more frequent in field and road borders than in the adjacent fields (Leveau & Leveau 2011).…”
Section: Introductionmentioning
confidence: 99%